1990
DOI: 10.1212/wnl.40.10.1561
|View full text |Cite
|
Sign up to set email alerts
|

Cortical tremor

Abstract: Two patients with action tremor that was thought to originate in the cerebral cortex showed fine shivering-like finger twitching provoked mainly by action and posture. Surface EMG showed relatively rhythmic discharge at a rate of about 9 Hz, which resembled essential tremor. However, electrophysiologic studies revealed giant somatosensory evoked potentials (SEPs) with enhanced long-loop reflex and premovement cortical spike by the jerk-locked averaging method. Treatment with beta-blocker showed no effect, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
167
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(188 citation statements)
references
References 0 publications
19
167
1
1
Order By: Relevance
“…Our patients developed an irregular tremor of the hands secondary to parietal cortical lesions, and these clinical features are similar to the features of cortical tremor originally described by Ikeda et al [7] as a postural and action tremor with a frequency of more than 8 Hz. It was reported as a variant of cortical reflex myoclonus in association with EEG abnormalities, seizure, abnormal SEPs and long latency EMG responses [8,9,10].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our patients developed an irregular tremor of the hands secondary to parietal cortical lesions, and these clinical features are similar to the features of cortical tremor originally described by Ikeda et al [7] as a postural and action tremor with a frequency of more than 8 Hz. It was reported as a variant of cortical reflex myoclonus in association with EEG abnormalities, seizure, abnormal SEPs and long latency EMG responses [8,9,10].…”
Section: Discussionsupporting
confidence: 89%
“…It was reported as a variant of cortical reflex myoclonus in association with EEG abnormalities, seizure, abnormal SEPs and long latency EMG responses [8,9,10]. In the cases of cortical tremor, the neuroimagings of the patients were reported normal, and specific EMG and EEG abnormalities were demonstrated [7,8,9,10]. However, both of our patients had parietal cortical lesions contralateral to the tremor.…”
Section: Discussionmentioning
confidence: 58%
“…1,2 Historically, various names have been given to the syndrome that show cortical myoclonic tremor and epilepsy: hereditary tremor with epileptiform seizures, 3 heredofamilial tremor and epilepsy, 4 cortical tremor, 5 familial essential myoclonus and epilepsy, 6 BAFME, 1 familial adult myoclonic epilepsy (FAME), 7 familial benign myoclonus epilepsy of adult onset, 8 familial cortical tremor with epilepsy, 9 autosomal dominant cortical myoclonus and epilepsy 10 and familial cortical myoclonic tremor with epilepsy (FCMTE). 11 Previous genetic studies, including our earlier report, 2 identified three different chromosomal loci, 8q 2,12 (BAFME, FCMTE1), 2p 10,13,14 (FCMTE2) and 5p 15 (FCMTE3) in Japanese, Italian and French pedigrees, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…2 BAFME was first reported in 1990 in the Japanese population. 3 Until now about 50 Japanese, 10 European families, and a French family were reported. 4 Previous studies revealed that BAFME was mapped to three chromosomal regions on chromosome 8, 5,6 chromosome 2, 7,8 and chromosome 5 4 in the Japanese, European and French populations, respectively.…”
Section: Introductionmentioning
confidence: 99%